Self-Perception, Psychosocial, Functional, Interest, and Knowledge Aspects Regarding Adults Orthodontic Treatment in Greater Jakarta - Sarah Jessica; Joko Kusnoto; Lia Hapsari Andayani (Journal of Indonesian Dental Association, 2024)
Introduction: Orthodontic treatment is the process of adjusting the position of the teeth and jaw to achieve optimal occlusion. Orthodontic treatment is generally performed on children and adolescents, but nowadays more adults are considering orthodontic treatment for aesthetic and dental health reasons. Factors that may influence the uptake of orthodontic treatment are cost, treatment time, gender, age, socioeconomic, knowledge, interest and psychological aspect. Objectives: This study aims to describe self-perception, psychosocial, functional, interest, and knowledge aspects regarding adults’ orthodontic treatment in greater Jakarta areas. Methods: This cross-sectional study was held from October to December 2023. Sample comprised 196 adults who met the following eligibility criteria: (a) aged 35-50 years; (b) living in greater Jakarta; (c) no history of orthodontic treatment; and (d) had income higher than minimum regional wage. Samples were taken by purposive sampling. Demographic data and information were collected by means of a validated questionnaire. The questionnaire is consisted of 31 items concerning self-perception, psychosocial, functional, interest, and knowledge aspects regarding orthodontic treatment. Results: Majority of respondents felt dissatisfied with the arrangement of their teeth (60.2%), felt that they needed orthodontic treatment (71.4%), felt that poor arrangement of teeth was related to decreased social attractiveness (89.3%), and did not had complaints when speaking (80.1%) or jaw joints (51.0%). The level of knowledge about orthodontic treatment was classified as poor (64.3%), and the majority of respondents were interested in undergoing orthodontic treatment (85.7%). Conclusion: Majority of adults aged 35-50 years in greater Jakarta areas are interested to undergo orthodontic treatment as well as having high self-awareness of the purpose of orthodontic treatment. The level of knowledge regarding orthodontic treatment among adults aged 35-50 years in greater Jakarta areas is poor.